U.S. Competitiveness in Science and Technology - Galama, Titus (RAND Corporation, 2008)
Is the United States in danger of losing its competitive edge in science and technology? This volume reviews the arguments surrounding this issue and contrasts them with relevant data, including trends in research and development investment; information on the size, composition, and pay of the U.S. science and engineering workforce; and domestic and international education statistics. The authors conclude with recommendations for policymakers.